2010
DOI: 10.1111/j.1744-9987.2009.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Density Lipoprotein Apheresis Decreases Ferritin, Transferrin and Vitamin B12, Which May Cause Anemia in Serially Treated Patients

Abstract: Clinical observations revealed an increased prevalence of iron deficiency anemia without chronic bleeding in patients treated with serial low-density lipoprotein (LDL) apheresis. Since several different proteins are adsorbed by LDL apheresis beside pro-atherogenic lipoproteins, we examined the modification of the full blood count, plasma iron, vitamin B12, folic acid, and hemolysis by LDL apheresis. Nineteen patients (55 (50-59) years, 4 female, 15 male) undergoing chronic LDL apheresis due to mixed dyslipidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…In contrast to data published by Bramlage et al [20] we saw a significantly lower decrease of transferrin by DALI when compared with the LF and HELP systems. On the other hand, the reduction pattern of ferritin was similar in both investigations (highest reduction by filtration methods).…”
Section: Discussioncontrasting
confidence: 85%
“…In contrast to data published by Bramlage et al [20] we saw a significantly lower decrease of transferrin by DALI when compared with the LF and HELP systems. On the other hand, the reduction pattern of ferritin was similar in both investigations (highest reduction by filtration methods).…”
Section: Discussioncontrasting
confidence: 85%
“…A German research group has very recently demonstrated that regular LDL apheresis reduces ferritin and iron levels [28] and a community study has indicated that anemia increases the risk for development of cardiovascular disease [29]. Furthermore, anemia increases the mortality in acute coronary syndromes [30].…”
Section: Hematological Parametersmentioning
confidence: 99%
“…(1) Blood loss due to blood remaining in the apheresis lines and repeated blood withdrawals (absolute ID) (2) Ferritin and transferrin loss though binding and removal with apheresis columns during LA (absolute ID) [5,6]. (3) Hemolysis during plasma separation or whole blood adsorption (absolute ID) (4) Anticoagulation in patients with history of cardiovascular events (absolute ID) [5].…”
Section: Introductionmentioning
confidence: 99%
“…(functional ID) [5]. (6) States of chronic inflammation (functional ID) (7) Insufficient dietary intake and/or absorption (absolute ID/functional ID)…”
Section: Introductionmentioning
confidence: 99%